2013
DOI: 10.1186/1471-2407-13-383
|View full text |Cite
|
Sign up to set email alerts
|

HRG-β1-driven ErbB3 signaling induces epithelial–mesenchymal transition in breast cancer cells

Abstract: BackgroundHeregulin (HRG; also known as neuregulin) is a ligand for ErbB3. One of its isotypes, HRG-β1, binds to ErbB3 and forms heterodimers with other ErbB family members, thereby enhancing the proliferation and tumorigenesis of breast cancer cells. HRG stimulation may contribute to the progression of epithelial–mesenchymal transition (EMT) and tumor metastasis in breast cancer. Majority of studies regarding EMT has been concentrated on TGF-β signaling. Therefore, we investigated whether the HRG-β1 and ErbB3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Studies using MCF-7 breast cancer cells ectopically overexpressing HRG, a model that mimics the scenario observed in human tumors, established prominent roles for the growth factor in motility and invasion. Furthermore, HRG promotes the secretion of matrix metalloproteases and confers metastatic properties on MCF-7 cells when inoculated into nude mice (10,(19)(20)(21)(22). Enhanced HRG/ErbB3 signaling has also been implicated in resistance to anticancer agents, including antiestrogens, ErbB tyrosine kinase inhibitors, and taxanes, and adaptive responses leading to drug resistance involve reprogramming of the kinome through reactivation of an HRG/ErbB3 axis (23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Studies using MCF-7 breast cancer cells ectopically overexpressing HRG, a model that mimics the scenario observed in human tumors, established prominent roles for the growth factor in motility and invasion. Furthermore, HRG promotes the secretion of matrix metalloproteases and confers metastatic properties on MCF-7 cells when inoculated into nude mice (10,(19)(20)(21)(22). Enhanced HRG/ErbB3 signaling has also been implicated in resistance to anticancer agents, including antiestrogens, ErbB tyrosine kinase inhibitors, and taxanes, and adaptive responses leading to drug resistance involve reprogramming of the kinome through reactivation of an HRG/ErbB3 axis (23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Induction of vimentin by HRG in this study was very weak and disappeared after 24 h (J. Kim et al, 2013). Besides, while in SKBr3 cells we observed strong induction of Snail after HRG treatment for 48 h, Kim et al did not see any difference between HRG-treated and the control group (J.…”
Section: 6) a Recent Study By Kim Et Al (Published After We Perfomentioning
confidence: 47%
“…Besides, this study showed induction of Snail, vimentin and fibronectin in response to HRG treatment (J. Kim et al, 2013). Induction of vimentin by HRG in this study was very weak and disappeared after 24 h (J.…”
Section: 6) a Recent Study By Kim Et Al (Published After We Perfomentioning
confidence: 53%
See 2 more Smart Citations